Coping strategies: A prospective study of patterns, stability, and relationships with psychological distress. Issue 2 (14th February 2014) - Nielsen, Morten B.; Knardahl, Stein
<x xml:space="preserve">Abstract</x> The aims of this article are: (1) to explore patterns (clusters) of coping strategies; (2) to examine the stability of individual coping strategies and patterns of coping over time; and (3) to establish long term associations between coping and psychological distress. Coping strategies were assessed with the Brief Cope questionnaire, whereas psychological distress was measured with the ten‐item version of the Hopkins Symptom Checklist, in a two‐year prospective sample comprising 3, 738 employees. Based on TwoStep cluster analysis of the Brief Cope, three different coping patterns were identified: low coping, engagement coping, and disengagement coping. Analyses of long‐term stability indicated malleable properties for the individual coping strategies as well as the three clusters. Disengagement coping strategies in the form of self‐blame and self‐distraction were most strongly associated with distress at follow‐up, whereas baseline distress was related to increased use of these strategies two years later. Coping patterns at baseline had no main effects on later levels of distress, but levels of distress at baseline predicted subsequent use of engagement and disengagement coping patterns. The finding that specific coping strategies are malleable suggests that it is possible to modify and develop dysfunctional strategies. The associations between disengagement coping strategies and distress indicate that this kind of coping is especially problematic with regard to mental health problems. A main contribution of this study is that it establishes cluster analytic techniques as beneficial in the assessment of coping.